Plant Growth Promoting Rhizobacteria and Silicon Synergistically Enhance Salinity Tolerance of Mung Bean - Mahmood, Sajid; Daur, Ihsanullah; Al-Solaimani, Samir G.; Ahmad, Shakeel; Madkour, Mohamed H.; Yasir, Muhammad; Hirt, Heribert; Ali, Shawkat; Ali, Zahir (Frontiers in Plant Science, 2016)
The present study explored the eco-friendly approach of utilizing plant-growth-promoting rhizobacteria (PGPR) inoculation and foliar application of silicon (Si) to improve the physiology, growth, and yield of mung bean under saline conditions. We isolated 18 promising PGPR from natural saline soil in Saudi Arabia, and screened them for plant-growth-promoting activities. Two effective strains were selected from the screening trial, and were identified as Enterobacter cloacae and Bacillus drentensis using matrix-assisted laser desorption ionization-time-of-flight mass spectrometry and 16S rRNA gene sequencing techniques, respectively. Subsequently, in a 2-year mung bean field trial, using a randomized complete block design with a split-split plot arrangement, we evaluated the two PGPR strains and two Si levels (1 and 2 kg ha-1), in comparison with control treatments, under three different saline irrigation conditions (3.12, 5.46, and 7.81 dS m-1). The results indicated that salt stress substantially reduced stomatal conductance, transpiration rate, relative water content, total chlorophyll content, chlorophyll a, chlorophyll b, carotenoid content, plant height, leaf area, dry biomass, seed yield, and salt tolerance index. The PGPR strains and Si levels independently improved all the aforementioned parameters. Furthermore, the combined application of the B. drentensis strain with 2 kg Si ha-1 resulted in the greatest enhancement of mung bean physiology, growth, and yield. Overall, the results of this study provide important information for the benefit of the agricultural industry.